Determinasi Inulin dalam Sampel Ekstrak Umbi Dahlia (Dahlia spp L.) yang Ditamam pada Media Tanah dan Polybag dengan Metode KLT- Densitometri - Arrofita Ani Sandiya; Yuni Retnaningtyas; Lestyo Wulandari (Pustaka Kesehatan, 2014)
Inulin is a polysaccharide , which is composed of fructose units. Inulin is generally found in plants family Compositae, Amirilidaceae, and Poaceae. Benefits inulin is as bifidogenic body, stimulate the immune system , relieve constipation , reduce the risk of osteoporosis . Inulin can be consumed alone as a prebiotic supplement. The purpose of this study was to develop a method for determination of inulin TLC-Densitometry in dahlia tuber extract samples (Dahlia spp L.) grown in soil media and polybag . Determination of inulin as a method of TLC densitometry using the stationary phase TLC plates Silica Gel F254, mobile phase = acetic acid glacial p.a: methanol p.a: aquabides sterille (v/v/v/v) (0,5:7,5:2) , solvent = Aquabides sterille: Ethanol 96 % p.a (3:1) v/v, apparition stains is mixed aniline in acetone 1% v/v:diphenylamine in acetone 10% b/v:phosphoric acid (5:5:1), and the wavelength () 380 nm . Validation of the method showed that the research procedures performed has had good linearity with a coefficient correlation 0.996 and Vx0 value 4.850%. This method also gives good accuracy and precision that is the percent recovery of inulin at 99,96%±0,39%. and the value of repeatability = 0,993% < 2,7% and intermediate precision RSD = 0,554% < 2,7% with limits of detection (LOD) and limit of quantitation (LOQ), respectively, 71,03 ng/spot and 236.76 ng/spot. The results showed levels of inulin in the dahlia tuber extract soil planted mediated by 86.256%±0.669% (%b/b±RSD%), and dahlia tubers grown polybag mediated by 76.146%±1.657% (%b/b±RSD%).